Simultaneous Determination of Alkenyl Benzenes in Essential Oils and Human Serum by Gas Chromatrography and GC-MS - Wang, Lai-Hao; Wang, Chia-Chen; Chuang, Shien-Kai (Asian Journal of Chemistry, 2010)
A gas chromatrography and GC-MS method have been developed for the simultaneous determination of fragrance containing alkenyl benzenes in commercial oils, as well as percutaneous absorption in humans after the application of an essential oil formulation. Nine alkenyl benzenes derivatives (estragole, trans-anethole, safrole, eugenol, methyl eugenol, isoeugenol, eugenyl acetate, myristicin and α-asarone) and seven other fragrances could be separation on an DB-5 column. A hierarchical cluster analysis established based on the GC-MS data from 23 samples essential oils.